Building the capacity of sub-national stakeholders in climate smart agriculture and climate information services - Mwongera, Caroline; Jalang'o, Dorcas; Kinyua, Ivy Wambui; Jaquet, Stéphanie; Mugo, Victor (2022)
This manual was created to support capacity building among sub-national stakeholders and contribute to the development and implementation of best-bet climate-smart agriculture and climate information services packages geared toward gender and social inclusion.